Morphological study of the effect of the cytoskeletal disrupting agent carbendazim on the oviduct of the Japanese quail (Coturnix coturnix japonica) - Madekurozwa, Mary-Catherine (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.